Use of Social Norms in the Production of Legal Norms : A Genealogical and Critical Approach to Nudges - Brunon-Ernst, Anne (Les Cahiers de droit, 2018)
The text looks into the conditions justifying the use of a social norm as the basis for establishing a legally binding rule. It starts with the definition of some key-terms (nudges, behavioural insights, social norms) before describing initiatives led by the UK Nudge Unit and other behaviourally-informed policies, such as default options, used in a legal context. This helps to highlight the type of problems related to the incorporation of social norms in legal norms, especially the importance of deviance to the social norm. Jeremy Bentham’s and Michel Foucault’s writings can be used to solve the problems raised. A framework can be devised to explain when a social norm can legitimately be incorporated in a legal norm. Indeed, beyond statistical evidence which identifies recurring patterns of behaviour, only a meta-norm can justify the choice of a legal norm. It is the efficacy of the norm which appears as a legitimising factor as it allows the promotion either of the productive forces in society (according to Foucault) or of utilitarian principles (according to Bentham). However, it seems that this meta-norm can be legitimately imposed only if it emanates from a strict deliberative discipline and is publicised. The article thus concludes that deliberation and publicity are the two means allowing to check that the legal norm complies with the meta-norm, thus legitimising the use of a social norm as a legally binding rule.